2020
DOI: 10.3390/cancers12113266
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in Cancer Patients: Effects on Disease Outcomes and Patient Prognosis

Abstract: The severity of coronavirus disease 2019 (COVID-19) symptoms and outcomes vary immensely among patients. Predicting disease progression and managing disease symptoms is even more challenging in cancer patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Cancer therapies, including chemotherapy, radiotherapy, and immunotherapy, often suppress the immune system, rendering cancer patients more susceptible to SARS-CoV-2 infection and the development of severe complications. However, data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 89 publications
1
28
0
Order By: Relevance
“…The finding that 24% and 39% of patients hospitalised with COVID-19 require follow-up care contrasts with estimates for all individuals diagnosed COVID-19 with COVID-19 from the UK (10%) 26 and the US (35%). 27 The findings also provide support for claims that older adults 3 and individuals with pre-existing health conditions 9 13 are more likely to experience ongoing COVID-19 complications requiring follow-up. Moreover, it was notable that this study’s GP attendees had higher readmission rates than those observed among the general population in previous studies.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The finding that 24% and 39% of patients hospitalised with COVID-19 require follow-up care contrasts with estimates for all individuals diagnosed COVID-19 with COVID-19 from the UK (10%) 26 and the US (35%). 27 The findings also provide support for claims that older adults 3 and individuals with pre-existing health conditions 9 13 are more likely to experience ongoing COVID-19 complications requiring follow-up. Moreover, it was notable that this study’s GP attendees had higher readmission rates than those observed among the general population in previous studies.…”
Section: Discussionsupporting
confidence: 61%
“…Immunocompromised populations (for example, people receiving cancer therapies such as chemotherapy, radiotherapy, and immunotherapy; and individuals with HIV) appear more likely to contract COVID-19. 8 , 9 Comorbidities such as hypertension, diabetes mellitus, cardiovascular diseases, and chronic obstructive pulmonary diseases are also common among those with COVID-19. 10 To compound matters, individuals with pre-existing health conditions are often more susceptible to severe COVID-19-related illness and injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 diagnosis in cancer patients is crucial for the prevention of the spread of the virus and the potential negative affect of the antineoplastic therapy on its course. Symptoms of COVID-19 in patients with malignancies very often are mild or absent, but cancer patients' mortality from complications of COVID-19 is more than twice as high as in the general population (5.6% vs. 2.3%, respectively) (20). The absence of specific clinical manifestations of COVID-19 in both general population and patients with malignant tumors in particular, create difficulties in infection detection.…”
Section: Coronavirus Diagnosis In Cancer Patientsmentioning
confidence: 99%
“…haematological cancers, as well as treatment-related immunosuppression, thus increasing risk of infection). [30] Patients with cancer have also been reported to be at increased risk of COVID-19 severity, including hospitalisation and death. [6][7][8][9] We found that cancer was associated with a higher risk of direct hospitalisation with COVID-19, regardless of years since cancer diagnosis; whereas only 1-5-year cancer patients had a higher risk of subsequent hospitalisation (following an outpatient diagnosis).…”
mentioning
confidence: 99%